NSM CFRP laminates for the shear strengthening of T section RC beams - Dias, Salvador J. E. (2006)
A new strengthening technique for concrete structures failing in shear was developed based on introducing laminate strips of carbon fiber reinforced polymer (CFRP) into slits made on the concrete cover of the lateral faces of the beams to be strengthened. This strengthening technique is designated Near Surface Mounted (NSM) and the laminate strips are fixed to concrete by epoxy adhesive. Exploratory tests with rectangular cross-section RC beams, conducted by the authors of the present work have shown that, in comparison to the externally bonded CFRP (EBR) technique, the NSM is easier and faster to apply, can mobilize higher percentage of the CFRP tensile strength, is more efficacy in terms of increasing the beams load carrying capacity, and assures higher resistance to vandalism acts. To assess the efficiency of NSM as a shear strengthening technique for real-case-situations, series of T cross section RC beams of 2.45 m span length were tested (Fig. 1). The influence of the percentage and inclination of the CFRP laminates on the increase of the beam shear resistance is analyzed. In the present work, this experimental program is described and the main results are presented and analysed. Fig. 2 represents the relationship between the shear resistance provided by the CFRP arrangements and the CFRP percentage for the three shear strengthening configurations analyzed. The obtained results indicate that: •Independently of the CFRP percentage and inclination of the laminates, NSM technique provided a significant contribution for the shear resistance of T section RC beams; •The beams with the highest CFRP percentage assured a maximum load 97%, 99% and 93% of the maximum load of 6S-R reference beam for the CFRP configurations of laminates at 90º, 60º and 45º, respectively (Fig. 3). The highest CFRP percentages had been designed to provide a maximum load similar to the one of 6S-R reference beam, with a reinforcing system composed of six steel stirrups; •After shear crack formation, the load carrying capacity of the beams shear strengthened with the highest CFRP percentage was significantly larger than the load carrying capacity of the 6S-R reference beam. This means that these CFRP shear strengthening arrangements contributed significantly for the increase of the beam stiffness after shear crack formation.